2018
DOI: 10.1038/s41598-017-19030-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bladder Carcinogens in the Urine of E-cigarette Users Versus Non E-cigarette Using Controls

Abstract: Electronic cigarette (EC) use is gaining popularity as a substitute for conventional smoking due to the perception and evidence it represents a safer alternative. In contrast to the common perception amongst users that ECs represent no risk initial studies have revealed a complex composition of e-cigarette liquids. Conventional cigarette smoking is a known risk factor for developing bladder cancer and prior reports raise concern some of those causative compounds may exist in EC liquids or vapor. Urine samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 17 publications
0
35
0
3
Order By: Relevance
“…Several studies found biomarkers indicative of combustible cigarette use in the e-cigarette-only groups, suggesting some study participants were undisclosed dual users or exposed to second-hand cigarette smoke [12,35]. An alternative explanation could also be that these biomarkers are truly present in e-cigarette users as well.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies found biomarkers indicative of combustible cigarette use in the e-cigarette-only groups, suggesting some study participants were undisclosed dual users or exposed to second-hand cigarette smoke [12,35]. An alternative explanation could also be that these biomarkers are truly present in e-cigarette users as well.…”
Section: Discussionmentioning
confidence: 99%
“…All 22 included studies were published since 2015. Participant mean/ median age was infrequently reported, but the median age of those reported was 36 yr [1,8,12,23,25,26,[31][32][33][34]. Study designs were primarily cross-sectional and longitudinal studies.…”
Section: Study Sourcesmentioning
confidence: 99%
See 3 more Smart Citations